2016
DOI: 10.1007/s00122-016-2678-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genotyping-by-sequencing permits cost-effective identification and discrimination of pasture grass species and cultivars

Abstract: A targeted amplicon-based genotyping-by-sequencing approach has permitted cost-effective and accurate discrimination between ryegrass species (perennial, Italian and inter-species hybrid), and identification of cultivars based on bulked samples. Perennial ryegrass and Italian ryegrass are the most important temperate forage species for global agriculture, and are represented in the commercial pasture seed market by numerous cultivars each composed of multiple highly heterozygous individuals. Previous studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…A number of studies have employed different depths of sampling within populations to accurately represent the genetic diversity within a variety/population and relationships between. Most recently, Pembleton et al (2016) demonstrated that 48 or more individual samples per ryegrass variety/population are required for such studies. As a consequence, a larger number (60 or more germinants per synthetic population) were harvested and subjected to pooled RNA extraction in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have employed different depths of sampling within populations to accurately represent the genetic diversity within a variety/population and relationships between. Most recently, Pembleton et al (2016) demonstrated that 48 or more individual samples per ryegrass variety/population are required for such studies. As a consequence, a larger number (60 or more germinants per synthetic population) were harvested and subjected to pooled RNA extraction in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The global genetic diversity of perennial ryegrass is large (Pembleton et al 2016) and so would require an extensive reference population. Diversity within a single breeding program should be lower, due both to sub-selection of founder genotypes from a broader range of germplasm, and the cyclic nature of many programs, such that individuals from pre-existing elite varieties are often chosen as parents for a next round of top-crosses.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been validated to be used in diversity (Elshire et al, 2011) and association studies (Hegarty et al, 2013; Morris et al, 2013) as well as advanced breeding application (Poland et al, 2012; Poland, 2015). A cost-effective targeted amplicons-based GBS approach was found very effective for genotyping perennial ryegrass and Italian ryegrass (Pembleton et al, 2016). Along with marker identification, GBS is a powerful tool to calculate genome-wide allele frequency of a particular locus.…”
Section: Genomics Tools and Resourcesmentioning
confidence: 99%
“…, , Pembleton et al. ). In most cases, cultivars have been effectively discriminated, although the resolution was limited for those varieties that have been derived from land races or ecotypes.…”
Section: Possible Applications Of Genomic Tools In Dus Testingmentioning
confidence: 99%
“…Later, based on the use of amplicon‐based genotyping‐by‐sequencing (GBS) approach on bulked seed samples, the NJ tree was extended to 63 cultivars of ryegrass, data being obtained at much lower cost (Pembleton et al. ). In both of the studies, two major cultivar‐specific groups were identified, corresponding to the two species (perennial and Italian ryegrass).…”
Section: Possible Applications Of Genomic Tools In Dus Testingmentioning
confidence: 99%